Impulse Buying MR. DIY Palu: Price Discount, Product Variety, dan Interior Display - Siti Nur Asiyah Naim; Makuri Sutomo; Rahmat Mubaraq; Asriadi Asriadi (Penerbit Goodwood, 2026)
Purpose: This study aims to explore the factors that drive impulse-buying behavior among customers at MR. DIY Palu by examining the influence of price discounts, product variety, and interior displays. Methodology/approach: The research was conducted at MR. DIY Palu using a quantitative approach and survey method. Data were collected through questionnaires distributed to 100 respondents using accidental sampling method. The analysis was carried out using multiple linear regression with SPSS software to determine the effect of price discount, product variety, and interior display on impulse buying. Results/findings: The results show that price discounts and product variety have a significant positive effect on impulse buying, while interior display does not significantly affect impulse buying behavior. Simultaneously, all three variables jointly influence consumer impulse buying at MR. DIY Palu. Limitations: This study focused only on MR. DIY Palu with a limited number of respondents and did not include other potential influencing factors such as psychological, situational, or demographic variables. Therefore, the findings may not be generalizable to all retail contexts or to other countries. Contributions: This study contributes to the fields of consumer behavior and retail marketing by providing empirical insights into the in-store factors that trigger impulse buying. These findings can assist retail managers in formulating effective strategies to increase spontaneous purchases and improve store performance. Conclusions: Overall, price discounts and product variety remain dominant drivers of impulse buying, emphasizing the importance of strategic pricing and diverse product offerings in retail environments.